Atomic layer deposition (ALD) of TiO2 films for photocatalytic application. - Choudhury Anshuman Das. (2009)
The field of photocatalysis can be traced back more than 80 years in history and during the past 20 years, it has become an extremely well researched field due to practical interest in air and water remediation, self-cleaning surfaces, and self-sterilizing surfaces. The following FYP project explores further in this field by conducting exploratory study on modifications to TiO2 catalysts with surface deposition of Palladium; (Pd-TiO2). Pd-TiO2 films were prepared by atomic layer deposition procedure followed sputter coating of Pd. The Pd–TiO2 film was well characterized by X-ray diffraction and atomic force microscope. It was found that Pd-TiO2 film possessed high photocatalytic activity and confirmed the application of H2 treatment on the deposited Pd further enhances photocatalytic activity. Three factors are identified as the underlying cause of the enhanced photocatalysis namely Pd-TiO2 interface charge separation, light scattering by Pd clusters on TiO2 surface, and the surface roughness of Pd deposited TiO2 nanofilm; though no conclusive deduction is made on the identity of predominant factor.